Botulinum toxin in the treatment of paralytic strabismus and essential blepharospasm - Thomas Ravi (Indian Journal of Ophthalmology, 1993)
As an alternative to conventional medical and surgical modalities that have met little success in the treatment of paralytic strabismus and essential blepharospasm, we explored the use of botulinum toxin as a treatment of choice in these two disorders. We used botulinum toxin in three patients with paralytic strabismus and in nine patients with essential blepharospasm. In three patients with paralytic strabismus, the botulinum toxin was injected into the ipsilateral antagonist of the paralysed muscle. The preinjection deviations ranged from 18 to 60 prism diopters. Two of these three patients achieved orthotropia around the thirtieth day and thereafter maintained it. The third patient became orthotropic on the eighteenth day, but deviation recurred and therefore required another injection of toxin. In nine patients with essential blepharospasm, botulinum toxin was injected into the orbicularis oculi muscles. Both objective and subjective improvement occurred in all nine patients within seven days and the effect lasted 12 to 15 weeks. Further injection of the toxin produced extremely beneficial results. However, the only significant complication that we encountered in both groups of strabismus and blepharospasm was ptosis, which was usually partial and temporary. From our experience, we advocate the use of botulinum toxin in the treatment of essential blepharospasm.